Ecotoxicological risk assessment of N-nitrosamines to Selenastrum capricornutum in surface waters: Insights into toxicity mechanisms and environmental Implications - Decai Liu; Litang Qin; Honghu Zeng; Yi Liang; Yanpeng Liang; Yingjie Chen; Huanfang Huang; Wenwen Chen (Ecotoxicology and Environmental Safety)
N-nitrosamines, one of the most common nitrogen-containing organic compounds in freshwater systems such as rivers or reservoirs, are toxic and carcinogenic to human. However, the aquatic hazard of these compounds to algae which is ubiquitous in surface water is still unclear. In this study, nine N-nitrosamines were investigated in the Pearl River Delta, China, with the total concentrations ranged from 27.0 to 727.6 ng/L. After that, four frequently detected N-nitrosamines—N-nitrosodiethylamine, N-nitroso-di-n-propylamine, N-nitrosopyrrolidine, and N-nitrosodibutylamine—were selected to explore their toxic mechanisms when individually or in combination exposed to Selenastrum capricornutum. The results revealed that the four N-nitrosamines and their mixtures all inhibited algal growth, with toxicity ranking as follows: N-nitrosodiethylamine > N-nitroso-di-n-propylamine > N-nitrosodibutylamine > N-nitrosopyrrolidine. Exposure to N-nitrosamines significantly altered the activities of superoxide dismutase and catalase and increased malondialdehyde levels. Additionally, total protein and photosynthetic pigment contents were significantly inhibited, especially under high-concentration exposure, leading to severe impairment of algal photosynthesis and growth. Toxicity modelling indicated that the quaternary mixture exhibited an additive effect on algal toxicity, with an inhibition of 15.6 % at environmental concentrations. However, risk quotients modeled using ECOSAR were significantly overestimated compared to experimental toxicity data. Risk assessments based on measured levels of N-nitrosamines in Pearl River Delta freshwater systems indicated that the risk quotients were all below 0.1. Nevertheless, the ecological risks posed by N-nitrosamines in mixture forms were slightly higher. This study represents the first systematic investigation into the hazardous effects of N-nitrosamines on algae and provides a scientific evaluation of their potential risks to freshwater ecosystems using experimental data.